Implementation of observation dependent visual object tracking using C++ - Lu, Chengyuan (2014)
Object tracking, an important task within the ﬁeld of computer vision, is the problem of estimating the position and other relevant information of moving objects in image sequences. It is widely used in smart vision systems such as visual surveillance, visual navigation, human-computer interaction and video compression.